2020
DOI: 10.1111/jhn.12761
|View full text |Cite
|
Sign up to set email alerts
|

Perceived dietary salt intake and the risk of primary liver cancer: a population‐based prospective study

Abstract: Background Although a high‐salt diet is associated with high risk of chronic diseases such as hypertension, stroke and cardiovascular disease, little is known about the relationship between a high‐salt diet and the risk of primary liver cancer (PLC). Consequently, we prospectively assessed the association of high perceived salt intake with the risk of PLC in the Kailuan Study. Methods In total, 97 006 participants who were healthy adults or free living adults at the baseline (2006) were included in the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…According to this viewpoint, the dietary salt recommendation for advanced cirrhosis patients is similar to that of the normal healthy population. In a population-based study, subjects with intermediate salt intake (6–10 g/d) and high salt intake (> 10 g/d) were found to have a higher risk of hepatocellular carcinoma with a multivariable hazard ratio (HR) of 1.49 and 1.9, respectively, compared to those with low salt intake (< 6 g/d)[ 37 ]. A recent cohort study from Iran reported that high dietary intake of salt (9.5–15 g/d) increases the rate of mortality in patients with cirrhosis (HR 2.26).…”
Section: Salt and Cirrhosis: Important Issuesmentioning
confidence: 99%
“…According to this viewpoint, the dietary salt recommendation for advanced cirrhosis patients is similar to that of the normal healthy population. In a population-based study, subjects with intermediate salt intake (6–10 g/d) and high salt intake (> 10 g/d) were found to have a higher risk of hepatocellular carcinoma with a multivariable hazard ratio (HR) of 1.49 and 1.9, respectively, compared to those with low salt intake (< 6 g/d)[ 37 ]. A recent cohort study from Iran reported that high dietary intake of salt (9.5–15 g/d) increases the rate of mortality in patients with cirrhosis (HR 2.26).…”
Section: Salt and Cirrhosis: Important Issuesmentioning
confidence: 99%
“…One study showed that consumption of caffeinated coffee with an extra two cups daily was positively associated with reduction in the risk of HCC, which was also shown with consumption of decaffeinated coffee to some extent ( 106 ). Another study showed that intermediate-salt (6-10 g/day) or high-salt (>10 g/day) intake displayed a higher risk to develop primary liver cancer compared to low-salt intake (<6 g/day), after adjusting other potential cofactors such as fatty liver, hypertension, and diabetes ( 107 ). Lifestyle intervention can effectively result in low body fat mass, reduction of visceral adiposity, and a decrease of metabolic diseases, including NAFLD, CVD, and T2DM ( 108 , 109 ); therefore, change of lifestyle plays an essential role in preventing HCC development.…”
Section: Treatmentsmentioning
confidence: 99%
“…Recently, studies proved a positive association between arterial hypertension and the development of several types of cancers including PLC (6)(7)(8). It is worth noting that high salt intake, a causal factor of hypertension, has also been proven to be closely related to the occurrence of several types of cancer (9)(10)(11). China is a fastgrowing and rapidly-aging nation with approximately 200 million hypertensive patients (12), and sodium intake is very high across all regions in China (12 g/person/d) (13).…”
Section: Introductionmentioning
confidence: 99%